Difference in Mathematical Creative Thinking Ability Students of MTs Negeri 7 Malang Reviewed by Gender - Rifqy, Muhammad Iqbal; Masamah, Ulfa (Faculty of Teacher Training and Education, 2024)
Creative thinking skills are crucial in modern education, driven by innovation demands and complex challenges, influenced by internal factors like motivation and emotional intelligence, and external factors like environment and gender. The fact shows that female students have a higher level of mathematical creative thinking than male students, both in the learning process and learning outcomes. This study aims to analyze the differences in mathematical creative thinking ability of MTs Negeri 7 Malang students in terms of gender perspective. Creative thinking ability consists of several aspects, namely fluency, flexibility, originality, and elaboration. This research used a qualitative approach with a case study type, involving four students who were selected using purposive sampling technique based on teacher criteria. Data were collected through written tests and interviews to explore mathematical creative thinking skills. The results showed that female students were more detailed in answering questions, more flexible in adopting alternative approaches, and more thorough and systematic in developing answers. Male students tended to show stronger originality skills with unique answers based on personal logic. These findings suggest the importance of a more inclusive and effective learning approach that considers gender differences in creative thinking.